Creative tools for producing realistic 3D facial expressions and animation. (2016) - Tsekleves, Emmanuel; Constantinides, Ricky; Cosmas, John
Creative exploration of realistic 3D facial animation is a popular but very challenging task due to the high level knowledge and skills required. This forms a barrier for creative individuals who have limited technical skills but wish to explore their creativity in this area. This paper proposes a new technique that facilitates users' creative exploration by hiding the technical complexities of producing facial expressions and animation. The proposed technique draws on research from psychology, anatomy and employs Autodesk Maya as a use case by developing a creative tool, which extends Maya's Blend Shape Editor. User testing revealed that novice users in the creative media, employing the proposed tool can produce rich and realistic facial expressions that portray new interesting emotions. It reduced production time by 25% when compared to Maya and by 40% when compared to 3DS Max equivalent tools.